2009
DOI: 10.1080/00016480802552576
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear reimplantations: technical and surgical failures

Abstract: Of 487 cochlear implantations, 3.8% of adults and 4.5% of children underwent a revision surgery. The mean time to device failure was 7.6 years in children and 1.5 year in adults. Causes of revision were seven hard failures, four soft failures, and nine medical reasons. Among the medical reasons, four patients had skin flap infection associated with an extended endaural approach. Audiologic performances were stable or improved following reimplantation in 90% of cases. We had two cases of electrode array misplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 13 publications
3
51
1
Order By: Relevance
“…In our series, 20.8 per cent of the The cochlear re-implantation incidence in this series is comparable to those reported by other studies. [3][4][5][6][7][8][9][10][11] However, the incidence of total device failure may be higher than figures published by some cochlear implant manufacturers. Indeed, the 3.9 per cent rate found in Nucleus patients was higher than the 0.2-2.4 per cent rate reported by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, 20.8 per cent of the The cochlear re-implantation incidence in this series is comparable to those reported by other studies. [3][4][5][6][7][8][9][10][11] However, the incidence of total device failure may be higher than figures published by some cochlear implant manufacturers. Indeed, the 3.9 per cent rate found in Nucleus patients was higher than the 0.2-2.4 per cent rate reported by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…The adult literature suggests a rate of CIri ranging from 4% to 13%. 4,5 Although some authors 6,7 have suggested that this rate is lower than that in the pediatric population, the CIri rate in children in other reports ranges from 4% to 15.4%. [7][8][9][14][15][16][17][18] Of these pediatric series, 7-9,14-18 surgical technique is not described except in 3 reports 8,14,18 that do not state whether suture fixation was used.…”
Section: Rate Of Ciri In Our Cohortmentioning
confidence: 95%
“…Overall complication rates requiring revision surgery vary from 3.8% to 5.1%, and a misplaced electrode is reported to be one of the most common major complications, next to device failure [1,2] . Previous case reports have described misplaced electrodes in the vestibule or semicircular canals.…”
Section: Introductionmentioning
confidence: 99%